The evaluation of the results of surgical treatment of forearm shaft fractures in children using elastic intramedullary stabilization - Graboń, Kamil; Mazur, Jan; Paczesny, Łukasz (Medical and Biological Sciences, 2014)
The vast majority of fractures of the forearm bones in juveniles may be treated conservatively immobilization in a cast. However, in some cases, surgical treatment is indicated because of the large displacement of fracture instability. The purpose of our study was to evaluate the surgical treatment of fractures of the forearm bones in children using flexible method intramedullary stabilization of patients on the basis of our branch. Material and methods: In years from 2002 - to 2011 129 patients were surgically treated because of forearm fractures. A group of 41 patients (32%) were studied in our branch. They have earlier had applied for phone call. Clinical assessment was given in the range of flexion and extension of wrist and elbow and forearm rotation range. It was investigated shake hands and subjective pain. These results were evaluated using the modified Fernandez - scale. The surgery was performed under general anesthesia. After setting fractures, the camera hood with a small skin incision was introduced into the marrow cavity of flexible steel wire stabilizing factions. The end of the wire after bending left under skin. Results: It was reported: 95,1% (n=38) were very good results and 4,9% (n=2) were good results and lack of medium and poor treatment. The patients in the study group, who suffered the most was the common limitation of forearm rotation (36,6%, n=15). One patient experienced a significant complication in the form of damage to the radial nerve dorsal knobs. All patients were satisfied with the outcome of treatment in their subjective opinion. Conlusions: In our opinion, flexible intramedullary stabilization of fractures of the forearm bones in children and adolescents is the method gives very good results of the treatment, minimally invasive and technically simple.